A multiscale numerical framework coupled with control strategies for simulating a wind farm in complex terrain. (15th July 2020) - Wang, Qiang; Luo, Kun; Yuan, Renyu; Wang, Shuai; Fan, Jianren; Cen, Kefa
Abstract: Improving the accuracy of the evaluation on the performance of wind farms in complex terrain under the actual atmosphere is crucial to the sustainable development of wind power. To this end, a multiscale numerical framework (MNF) integrating the WRF model coupled with a wind farm parameterization and a LES model embedded with the wind turbine control strategies is developed. An interface for data exchange between the WRF and LES models is established. The simulated nacelle velocity and the generator power results agree well with the observations, proving that the MNF is capable of assessing the flow behavior and performance of a realistic onshore wind farm in complex terrain. Besides, the impacts of terrain on the operating process for wind turbines over the hill under the dynamic inflow condition are quantified. The results show that the wind turbine at the top of the hill can cut in the rated-state earlier and cut out later, which improves the power output by 5.5%, indicating that the total generation of wind farms can be enhanced by making full use of terrain acceleration. This high-fidelity multiscale numerical framework is expected to be an effective tool for the siting and optimization of wind farms. Highlights: A multiscale numerical framework for simulating wind farms is built. The wind turbine control strategy is coupled into this framework. The accuracy of the multiscale numerical framework is validated. The flow behavior and power of a realistic wind farm are examined. The impact of terrain on the operating process is quantified.